MANAGING INTRAOPERATIVE FLOPPY IRIS SYNDROME WITH I-RING PUPIL DILATOR - Trpenoski, Naum (Horizons - International Scientific Journal, 2020)
Background: Intraoperative floppy iris syndrome (IFIS) is characterized by iris prolapse through the intraoperative section, as well as by progressive intraoperative miosis during cataract surgery. Purpose: To estimate the effectiveness of I-Ring pupil dilator in patients that were treated with tamsulosin and having IFIS during cataract surgery. Method: Eighty patients were included in the study; 40 patients were without (control group) and 40 patients were treated with application of I-Ring mechanic pupil dilator intraoperatively. Pre- and postoperative best corrected visual acuity (BCVA), intraoperative and postoperative pupil diameter and complications were evaluated in each patient. Results: Intraoperative complications occurred in 40% and postoperative complications in 30% of patients in the control group. In the treated group there were no intra or postoperative complications. BCVA and pupil diameters were not significantly different among the two groups. Conclusion: I-Ring pupil dilators are highly effective for prevention of complications in patients with IFIS.